Agent-based active-vision system reconfiguration for autonomous surveillance of dynamic, multi-object environments - Bakhtari, A.; Benhabib, B. (2005 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2005)
This paper presents a novel method for the coordinated selection and positioning of groups of active-vision cameras for the surveillance of an object-of-interest as it travels through a multi-object environment with an a priori unknown trajectory. Dynamic sensing-system reconfiguration is achieved through the use of multiple real and virtual agents. The proposed reconfiguration algorithm is implemented on an experimental prototype setup for automated facial recognition of a single subject in a cluttered environment.